Mining tax regime reforms - de facto nationalisation - Mendes, Tania Flores (My University, 2015)
Cannot copy abstract
Thesis (M.Com. (Taxation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2014.
Keywords: Nationalisation; Mining-tax regime reforms; SIMS report; Foreign precedent